MAXIMUM POWER POINT TRACKING (MPPT) UNTUK GENERATOR DC - Silpita Marastika; Marsyandha Widyanurrahmah; I Made Andik Setiawan; Zanu Saputra (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
DC generator is a device that can change over mechanical energy into electrical energy. To be utilized as elecrical energy, a mechanical energy is required that comes from the revulotion of the rotor from a DC generator. The rotation of this DC generator is always changing or not constant. So that the power that comes out of the rotation of the rotor isn’t ideal. One way to maximize the power from the DC generator output is to find the maximum power point at the DC generator output. This final project has the objective of being able to discover the greatest point at the DC generator output, maximum power point tracking (MPPT) utilizing the Perturb and Observe (PO) algorithm. To find the maximum point in the final project, components are needed, namely a DC generator, Buck-Boost Converter XLSEMI 6019, connection sensor, INA219 Current Sensor, and a resistor as a load that will be controlled by Arduino Mega 2560. By using the PO algorithm this final project can be made to displays maximum power, maximum current, and maximum voltage.